MULTIKULTURALISME DALAM PERSPEKTIF ISLAM - Achmad Yusuf (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
Indonesia is inhabited by a pluralist society and the majority of Moslems, but there are groups who say that multiculturalism is a western idea that does not exist in Islam. They forbid following multiculturalism because according to certain groups and not in accordance with the Qur’an and Hadith. The implications of this superficial understanding of Islam can lead to conflicts in the name of religion, and can lead to religious exclusiveness. The purposes of this study are (a) How to understand multiculturalism and (b) how is multiculturalism in Islamic perspective. The conclusion of this study are (a) Multiculturalism is the concept where communities in the context of nationality can recognize, and accept the diversity, diversity, plurality of cultures, races, religions and languages in pluralist nations. (b) Multiculturalism within the Islamic perspective has existed since Alqur’an was revealed, and contained in Hadits.